Personal and interpersonal value system, self-perception and identity of Spanish nurses: a cross-sectional study - Losa Iglesias, Marta Elena (Journal of beliefs and values, 2011)
The aim of this research is to identify the predominant values system among a sample of Spanish nurses, to identify how values are tied to professional nursing identity and determine differences in values and identity between socio-demographic variables as a gender, citizenship and/or nursing service. Cross-sectional study was performed with a randomised sample of 337 staff nurses who had worked for a minimum of one year in adult or paediatric services in the public or private health care system in the Northern State in Spain. Gordon’s Personality Inventory was administered to measure the personal, interpersonal and self image of sample. The study found differences in personal and interpersonal values across generational cohorts, gender and ethnic group. Evidence of feminisation of values among male nurses was also found - in terms of age and professionally, they may take fewer risks and show a tendency toward congruence with the predominant organisational culture.